2015
DOI: 10.1007/s10064-015-0735-8
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the flow behavior of a simulated municipal solid waste

Abstract: Flow slides in the municipal solid waste (MSW) landfill are common geological disasters that have the potential to cause loss of life, destruction of property, and damage to the natural environment in the surrounding region. In this work, a mixture of peat, kaolin clay and quartz sand was used as a model test material to simulate MSW. A series of physical model tests on MSW simulant flows was carried out to capture the run-out behavior of the waste and analyze its mobility. The testing assembly consisted of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 59 publications
0
12
0
Order By: Relevance
“…Landfill slope failure at MSW dumpsites can be found in previous studies, wherein six reported cases between 1993 and 2005 resulted in approximately 500 deaths and significant economic loss (Blight, 2008;Blight and Fourie, 2005;Eid et al, 2000;Kjeldsen and Fischer, 1995;Kocasoy and Curi, 1995;Merry et al, 2005;Mitchell et al, 1990). The deadliest event in history killed 278 people in Manila, Philippines, in 2000, and the second deadliest event killed 143 people and buried 71 houses on 21 February 2005 at the Leuwigajah dumpsite near Bandung, Indonesia (Lavigne et al, 2014).…”
Section: Introductionmentioning
confidence: 79%
See 4 more Smart Citations
“…Landfill slope failure at MSW dumpsites can be found in previous studies, wherein six reported cases between 1993 and 2005 resulted in approximately 500 deaths and significant economic loss (Blight, 2008;Blight and Fourie, 2005;Eid et al, 2000;Kjeldsen and Fischer, 1995;Kocasoy and Curi, 1995;Merry et al, 2005;Mitchell et al, 1990). The deadliest event in history killed 278 people in Manila, Philippines, in 2000, and the second deadliest event killed 143 people and buried 71 houses on 21 February 2005 at the Leuwigajah dumpsite near Bandung, Indonesia (Lavigne et al, 2014).…”
Section: Introductionmentioning
confidence: 79%
“…The porosity and water content of MSW is typically high in an unregulated landfill because of inadequate drainage system, and therefore failures of MSWs commonly exhibit flowlike behaviors, i.e., flowslide, with extremely high mobility (e.g., Dai et al, 2016;Huang and Cheng, 2017). Landfill slope failure at MSW dumpsites can be found in previous studies, wherein six reported cases between 1993 and 2005 resulted in approximately 500 deaths and significant economic loss (Blight, 2008;Blight and Fourie, 2005;Eid et al, 2000;Kjeldsen and Fischer, 1995;Kocasoy and Curi, 1995;Merry et al, 2005;Mitchell et al, 1990).…”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations